Extracellular domain of EpCAM enhances tumor progression through EGFR signaling in colon cancer cells. (1st October 2018) - Liang, Kang-Hao; Tso, Hsien-Cheng; Hung, Shao-Hsi; Kuan, I.-I.; Lai, Jun-Kai; Ke, Feng-Yi; Chuang, Yi-Ting; Liu, I-Ju; Wang, Yi-Ping; Chen, Ruey-Hwa; Wu, Han-Chung
Abstract: Epithelial cell adhesion molecule (EpCAM) is highly expressed in colon cancers, but its role in cancer progression remains to be elucidated. In this work, we found that the extracellular domain of EpCAM (EpEX) activated EGFR and downstream ERK1/2 signaling to promote colon cancer cell migration and proliferation, as well as tumor growth. Mechanistically, we discovered that EpEX-EGFR-ERK1/2 signaling positively regulated intramembrane proteolysis (RIP) of EpCAM and shedding of the intracellular domain (EpICD). Treatment with an EGFR inhibitor ablated the EpEX-induced phosphorylation of ERK1/2 and AKT. Additionally, treatment with inhibitors of either EGFR or MEK decreased EpEX-induced EpICD shedding and further revealed that EpICD is necessary for nuclear accumulation of β-catenin and the induction of HIF1α target gene expression in vitro and in vivo . Moreover, an anti-EpCAM neutralizing monoclonal antibody, EpAb2-6, inhibited the nuclear translocation of EpICD and β-catenin and induced apoptosis in colon cancer cells. Importantly, analysis of colorectal cancer tissues showed that nuclear accumulation of EpICD was highly correlated with metastasis and poor prognosis, suggesting that it may play an important functional role in cancer progression. Thus, we provide novel insights into the mechanisms and functions of EpEX-mediated signaling, which may be considered as a promising target for the treatment of colon cancer. Highlights: EpEX enhances proteolytic cleavage of EpCAM via an EGFR-dependent pathway. EpICD promotes β-catenin nuclear translocation and hypoxia-related genes expression. Nuclear EpICD correlates with metastasis and poor prognosis of CRC patients.